2023
DOI: 10.3390/antiox12122102
|View full text |Cite
|
Sign up to set email alerts
|

Development of Pharmacological Strategies with Therapeutic Potential in Ischemic Stroke

Alejandro Escobar-Peso,
Emma Martínez-Alonso,
Jaime Masjuan
et al.

Abstract: Acute ischemic stroke constitutes a health challenge with great social impact due to its high incidence, with the social dependency that it generates being an important source of inequality. The lack of treatments serving as effective neuroprotective therapies beyond thrombolysis and thrombectomy is presented as a need. With this goal in mind, our research group’s collaborative studies into cerebral ischemia and subsequent reperfusion concluded that there is a need to develop compounds with antioxidant and rad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 62 publications
0
1
0
Order By: Relevance
“…The key mechanism in the formation of ischemic stroke is oxidative stress [ 112 ], which also causes neuronal apoptosis, inflammation, and nerve injury [ 113 ]. It was reported that OA reduced cerebral ischemic stroke damage by increasing the level of mitochondrial antioxidant α-tocopherol (α-TOC) and GSH, as well as decreasing the leakage of the damage marker lactate dehydrogenase (LDH) [ 114 ].…”
Section: Anti-cardiovascular Diseases Effectsmentioning
confidence: 99%
“…The key mechanism in the formation of ischemic stroke is oxidative stress [ 112 ], which also causes neuronal apoptosis, inflammation, and nerve injury [ 113 ]. It was reported that OA reduced cerebral ischemic stroke damage by increasing the level of mitochondrial antioxidant α-tocopherol (α-TOC) and GSH, as well as decreasing the leakage of the damage marker lactate dehydrogenase (LDH) [ 114 ].…”
Section: Anti-cardiovascular Diseases Effectsmentioning
confidence: 99%